Modelos de sistemas agroflorestais com fins apícolas para o município de Pedreira-SP - Cassiani, Leopoldo Nobile (Universidade Federal de São Carlos, 2008)
The rural area of the municipality of Pedreira presents its fragmented landscape caused by agricultural expansion occurred in the region at the time of deploying cafezais and then pastures. Thus a proposal for agroforestry systems with potential beekeeping presents itself as a highly recommended strategy in the recovery of degraded areas coupled with the increase of income through beekeeping addition to environmental services generated by the activity. The general objectve of this study was to draw up designs for agroforestry purposes with bee and analyze the specific objective ethnobotanical knowledge of farmers and beekeepers on local conditions, as a starting point for implementation and execution of plans for recovery of degraded areas, with focus in Areas of Protection Permanent and Legal Reserve. The proposal agroforestry systems with potential beekeeping are likely to be implemented considering the multifunctional to serve, from the legal aspects, ecological, economic and social.
Models of agroforestry system with beekeeping purpose to municipality of pedreira-sp
Keywords: Sistemas agroflorestais; Abelha - criação; Legislação ambiental; Conhecimento etnobotânico; Apicultura; Agroforestry system; Ethnobotanical knowledge; Apiculture; CIENCIAS AGRARIAS